An ultra‐high performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry identification and characterization of the active constituents from Abrus mollis Hance. Issue 2 (14th November 2022) - Tan, Zhien; Chen, Shimin; Zhang, Mengli; Qu, Xiaosheng; Li, Taiping; Zhang, Aihua; He, Yanmei; Ou, Min; Long, Lihuo; Chen, Lu; Wu, Fangfang
Abstract : Abrus mollis Hance is a traditional Chinese medicine that is widely used to treat acute and chronic hepatitis, steatosis, and fibrosis. Its therapeutic qualities of it have long been acknowledged, although the active ingredients responsible for its efficacy and the mechanisms of its action are unknown. In this study, the chemical constituents absorbed into the blood from Abrus mollis Hance were assessed by using liquid chromatography‐quadrupole‐time‐of‐flight mass spectrometry and the data was analyzed with the UNIFI screening platform. The results obtained were compared to existing chromatographic‐mass spectrometry information, including retention times and molecular weights as well as known reference compounds. 41 chemical constituents were found in Abrus mollis Hance, and these included 16 flavonoids, 13 triterpenoids, five organic acids, and two alkaloids. Experimentally it was found that Abrus mollis Hance had a therapeutic benefit when treating α‐naphthalene isothiocyanate‐induced acute liver injury in rats. In addition, 11 blood prototypical constituents, including six flavonoids, three triterpenoids, and two alkaloids, were found in serum samples following intragastric administration of Abrus mollis Hance extracts to rats. This novel study can be used for the quality control and pharmacodynamic assessment of Abrus mollis Hance in order to assess its efficacy in the therapeutic treatment of patients.